Solid waste research in Scopus (2002-2023): A study based on the Peru scientific production - Arista-López, Deivis Robin (Iberoamerican Journal of Science Measurement and Communication, 2025)
Objective. In this study, we performed a bibliometric analysis of the Peruvian scientific production of solid waste. Methodology. A bibliometric analysis was conducted based on records indexed in the Scopus database from 2003 to 2023. The bibliometric indicators examined were productivity by journals, productivity by institutions, productivity by authors, most cited articles, and co-occurrence of terms. Results. Many journals and international conferences oriented from marine biology to ecological engineering stood out among the sources with the highest productivity. Three institutions stood out: Universidad Privada del Norte, Pontificia Universidad Católica del Perú, and Universidad San Ignacio de Loyola. There is a group of public universities that stood out, such as Universidad Nacional de Ingeniería, Universidad Nacional Mayor de San Marcos, Universidad Nacional Agraria La Molina, Peru, and Universidad Nacional del Centro del Perú. A small group of leading authors was observed: De-la-Torre, G.E., Vázquez-Rowe, I.; Marin, M.V., and Ziegler-Rodriguez, K. The most cited articles were related to the energetic use of agricultural waste, contamination by personal protective equipment waste during the COVID-19 pandemic, solid waste management in Latin America, environmental impact and public health of plastic waste related to COVID-19, and waste management evaluation and optimization. The co-occurrence map of terms revealed eight thematic clusters: (1) intersection between agriculture and waste management, (2) chemical processes in waste reduction, (3) waste management in aquatic environments, (4) intersection between agriculture and waste management with emphasis on approaches, practices and strategies, (5) agro-industrial waste, (6) impact of solid waste on air and water pollution, (7) social perspectives on environmental issues, and (8) eco-efficiency in the construction sector. Conclusions. Peruvian research on solid waste strongly focuses on agriculture, given that these issues were highlighted in three of the eight thematic clusters identified.